Mifologik bilim tuzilmalarining frazeologik sathda voqe’lanishi (Qadimgi yunon mifologiyasi misolida) - Toshxo‘jayeva N.M (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
This article is devoted to the problems of semantic classification of phraseological units with a mythologeme component, which is one of the most important levels of the lexicon. The author explains the term phraseological unit and also provides information about their linguistic and cultural significance. As a result of the research, a unique semantic classification of phraseological units with a mythologeme component, such as naming the factors affecting a person and his life activity, having symbolic meaning, and representing mythological beings, was developed.